Minimum wages and employment in France and the United States - Abowd, John M. 1951-; Kramarz, Francis; Margolis, David N. (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1999)
We use longitudinal individual wage and employment data in France and the United States to investigate the effect of changes in the real minimum wage on an individual's employment status. We find that movements in both French and American real minimum wages are associated with mild employment effects in general and very strong effects on workers employed at the minimum wage. In the French case, a 1% increase in the real minimum wage decreases the future employment probability of a man (respectively, a woman) currently employed at the minimum wage by 1.3% (1.0%). In the United States, a decrease in the real minimum wage of 1% increases the probability that a man (woman) employed at the minimum wage came from unemployment in the previous year by 0.4% (1.6%).